Unifying Theories of Programming 5th International Symposium, UTP 2014, Singapore, May 13, 2014, Revised Selected Papers - Naumann, David (Springer, 2015)
This book constitutes the refereed proceedings of the 5th International Symposium on Unifying Theories of Programming, UTP 2014, held in Singapore, Singapore, in May 13, 2014, co-located with the 19th International Symposium on Formal Methods, FM 2014. The 7 revised full papers presented together with one invited talk were carefully reviewed and selected from 11 submissions. They deal with numerous formal notations and theories of programming, such as abstraction, refinement, choice, termination, feasibility, locality, concurrency and communication.